2014
DOI: 10.1590/1415-52732014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol reduces chronic inflammation and improves insulin action in the myocardium of high-fat diet-induced obeserats

Abstract: A B S T R A C T ObjectiveTo evaluate the effects of resveratrol on insulin signaling and inflammation pathway in the myocardium of high-fat diet-induced obese rats. MethodsThirty Wistar rats were divided into a control group (n=10, standard diet), obese group (n=10, high-fat diet), and obese supplemented with resveratrol group (n=10, 20 mg/kg/day) for eight weeks. An insulin tolerance test was performed at the end of the study period "0" (without insulin), 5, 10, 15, 20, 25, and 30 minutes after an intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This molecule has shown pleiotropic and beneficial effects on both type 2 diabetes and cardiovascular complications [9]. Various studies, using models of type 2 diabetes or metabolic syndrome, showed that RSV could decrease chronic inflammation [10], improve insulin sensitivity [11], lipid profile [12], and decrease oxidative stress [13]. Other studies also demonstrated the effects of RSV on endothelial function mainly through mechanisms involving nitric oxide (NO) and sirtuin pathways [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…This molecule has shown pleiotropic and beneficial effects on both type 2 diabetes and cardiovascular complications [9]. Various studies, using models of type 2 diabetes or metabolic syndrome, showed that RSV could decrease chronic inflammation [10], improve insulin sensitivity [11], lipid profile [12], and decrease oxidative stress [13]. Other studies also demonstrated the effects of RSV on endothelial function mainly through mechanisms involving nitric oxide (NO) and sirtuin pathways [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%